Contrasting healthcare costs of COPD and asthma in elderly - Mattila Tiina; Vasankari Tuula; Herse Fredrik; Leskelä Riikka-Leena; Erhola Marina; Avellan-Hietanen Heidi; Toppila-Salmi Sanna; Haahtela Tari (Elsevier, 2025)
Background
Caring for ageing populations creates new challenges for society. Obstructive pulmonary diseases, asthma and especially COPD, are responsible for considerable morbidity, mortality, and financial costs in the elderly. We present the change in the burden of asthma and COPD in those aged ≥60 years in Finland from 1996 to 2018.
Methods
We collected national register data from 1996 to 2018 from Statistics Finland, Care Register for Health Care, and the Social Insurance Institution. We estimated the prevalence of asthma and severe COPD, use of healthcare, social services, reimbursed inhalation medications, and societal costs.
Results
In subjects aged ≥60 years, the prevalence was 8% for asthma with reimbursed medication and 0·7% for severe COPD in 2018. In 1996–2018, total costs increased from 33 M€ to 58 M€ (+57%) for asthma and decreased from 38 M€ to 30 M€ (−27%) for COPD. Costs per patient decreased for asthma from 720 € to 460 € (−57%) and remained stable for COPD (2700 € in 2018). Potential years of life lost (PYLL) increased in COPD from 5000 to 6400 (+28%) and the number of emergency department visits increased from 3700 to 6000 (+62%).
Conclusions
In a population aged ≥60 years, the total burden caused by asthma decreased but remained stable and high in COPD. PYLL and visits in emergency care increased in COPD.